2021
DOI: 10.1136/jitc-2020-001696
|View full text |Cite
|
Sign up to set email alerts
|

Frequent amplification of HDAC genes and efficacy of HDAC inhibitor chidamide and PD-1 blockade combination in soft tissue sarcoma

Abstract: BackgroundThe advent of immune checkpoint therapy has been a tremendous advance in cancer treatment. However, the responses are still insufficient in patients with soft tissue sarcoma (STS). We aimed to identify rational combinations to increase the response to immune checkpoint therapy and improve survival.MethodsWhole-exome sequencing (WES) was performed in 11 patients with liposarcoma. Somatic copy number alterations (SCNAs) were analyzed at the gene level to identify obvious amplification patterns in drug-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 41 publications
0
43
0
Order By: Relevance
“…Several studies have demonstrated that treatment with HDACi dampens the anti-tumor immune response by upregulation of PD-1 on T cells ( 38 , 39 ). Thus, PD-1/PD-L1 blocking antibodies and HDACis have synergistic effects in the treatment of different cancers ( 38 , 39 ). Additionally, VPA treatment blocked the function of myeloid-derived suppressor cells and made tumor cells susceptible to anti-PD-L1 immunotherapy ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that treatment with HDACi dampens the anti-tumor immune response by upregulation of PD-1 on T cells ( 38 , 39 ). Thus, PD-1/PD-L1 blocking antibodies and HDACis have synergistic effects in the treatment of different cancers ( 38 , 39 ). Additionally, VPA treatment blocked the function of myeloid-derived suppressor cells and made tumor cells susceptible to anti-PD-L1 immunotherapy ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing the drug sensitivity data, we speculated that HDAC inhibitors might enhance ICI efficacy and even reverse the poor response of low-GMS patients to ICI treatment, which was consistent with our GSEA results ( Figures 5A–C ). Some studies have reported HDAC inhibitors’ potential in enhancing the efficacy of immunotherapy and even reverse the insensitivity to ICI ( Ugurel et al, 2019 ) by enhancing the anti-tumor activity of CD8 + T cells ( Que et al, 2021 ) and NK cells ( Hicks et al, 2018 ; Kim et al, 2020 ), reducing the number of M2 macrophages ( Knox et al, 2019 ; Kim et al, 2020 ), impairing the immunosuppressive function of MDSCs ( Kim et al, 2020 ; Que et al, 2021 ) and increasing the expression of PD-L1 on tumor cells ( Hicks et al, 2018 ; Que et al, 2021 ). Two clinical studies investigated the efficacy of HDAC inhibitor vorinostat, combined with immunotherapy, demonstrating preliminary antitumor activity ( Gray et al, 2019 ; Rodriguez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The other research group also reported the efficacy of HDAC inhibitor on liposarcoma cell lines by medium-scale high-throughput drug screening [41]. A recent study reported that the HDAC gene family was amplified in sarcomas, including in DDLPS, and that the combination of HDAC inhibitor and anti-PD1 therapy promoted tumor regression [42]. Another study suggested that HDAC inhibition reduced MDM2 expression and tumor growth in DDLPS [43].…”
Section: Discussionmentioning
confidence: 99%